Rate of Magma Supply Beneath Mammoth Mountain, California, Based on Helium Isotopes and CO2 Emissions. Issue 9 (8th May 2019) - Lewicki, Jennifer L.; Evans, William C.; Montgomery‐Brown, Emily K.; Mangan, Margaret T.; King, John C.; Hunt, Andrew G.
Abstract: Mammoth Mountain, California, has exhibited unrest over the past ~30 years, characterized by seismicity over a broad range of depths, elevated 3 He/ 4 He ratios in fumarolic gas, and large‐scale diffuse CO2 emissions. This activity has been attributed to magmatic intrusion, but minimal ground deformation and the presence of a shallow crustal gas reservoir beneath Mammoth Mountain pose a challenge for estimating magma supply rate. Here, we use the record of fumarolic 3 He/ 4 He ratios and CO2 emissions to estimate that of the ~5.2 Mt of CO2 released from Mammoth Mountain between 1989 and 2016, 1.6 Mt was associated with active intrusion and degassing of ~0.05–0.07 km 3 of basaltic magma. Intrusion at an average rate of ~0.002–0.003 km 3 /year into a postulated zone of partial melt at ~15‐km depth could occur without detection by local Global Navigation Satellite System stations. Plain Language Summary: Magma supply rate exerts a fundamental control on a volcano's eruptive and intrusive activity. Seismicity and large‐scale diffuse CO2 emissions at Mammoth Mountain, California, over the past ~30 years have been attributed to magmatic intrusion. Estimating magma supply rate beneath Mammoth Mountain is challenging, however, because (1) ground deformation, a useful indicator of magmatic intrusion, has been minor and (2) a gas reservoir in the shallow crust traps rising CO2 for unknown periods. In this study, we use fumarole helium isotopes to estimate CO2 emissions associated with active magmatic intrusion beneath Mammoth Mountain from 1989 to 2016, volume of basaltic magma degassed, and average intrusion rate. Based on ground deformation source modeling, we find that this rate of intrusion could potentially occur into a postulated zone of partial melt at ~15‐km depth without detection by geodetic monitoring, although other (e.g., deeper) sources are possible. Key Points: Fumarole helium isotopes are used to quantify CO2 emissions associated with active magmatic intrusion beneath Mammoth Mountain From 1989 to 2016, ~1.6 Mt of CO2 emissions was associated with active intrusion and degassing of ~0.05‐0.07 km 3 of basaltic magma An average intrusion rate of ~0.002‐0.003 km 3 /year into a zone of partial melt at ~15‐km depth might occur undetected by geodetic monitoring